EFEKTIVITAS MODEL KOOPERATIF TIPE TEAMS GAMES TOURNAMEN (TGT) DALAM MENINGKATKAN HASIL BELAJAR KOGNITIF SISWA KELAS XI SMAN 2 SAWAHLUNTO PADA MATA PELAJARAN GEOGRAFI - Ella Marsalina; Afdhal (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effectiveness of the Teams Games Tournament (TGT) cooperative learning model in improving students' cognitive learning outcomes in Geography for Grade XI at SMAN 2 Sawahlunto. The background of this study is the low cognitive learning outcomes of students caused by a lack of variety in learning models and low student engagement in the learning process. This study employs a quantitative approach using an experimental method and a pretest-posttest control group design. The research sample consists of two classes: XI.F4 as the experimental class and XI.F5 as the control class, with a total of 67 students. Data were collected through pretest and posttest assessments and analysed using descriptive statistical tests, normality tests, homogeneity tests, t-tests, and N-Gain tests. The results of the study indicate that the implementation of the TGT model significantly improves students' cognitive learning outcomes. The posttest average of the experimental class reached 86.94 with a completion rate of 91%, compared to the control class, which only reached an average of 70.42 with a completion rate of 7%. The N-Gain value of the experimental class was 0.72, which is classified as quite effective. Thus, the TGT cooperative learning model has been proven to be effective in improving students' cognitive learning outcomes in Geography.